The Influence of a Principal's Transformational Leadership Style on Teacher Performance in the Digital Era: A Case Study - Habibah, Sitti; Juhari, Agusalim (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Transformational leadership is believed to enhance motivation and performance; however, it is essential to evaluate the efficacy of the high school principal's leadership style in motivating teachers, particularly in the integration of technology and the resolution of digital learning challenges.  This study analyzes and empirically tests the principal's transformational leadership style on teacher performance at High School 2 Takalar, especially in the digital age when technology adaptation and learning innovation are crucial. This study uses a quantitative approach with an associative explanatory survey design. The total number of teachers at High School 2 Takalar is 78, with 21 men and 57 women. The research sample was determined using the Slovin Formula with a tolerance level of error of 10% (e = 0.10), resulting in a minimum of 44 respondents. Data was collected through a closed questionnaire and analyzed using simple linear regression statistical techniques. The study found a positive and significant relationship between principal transformational leadership and teacher performance. Teacher performance in technology adaptation, learning innovation, and main task implementation improved significantly with increased transformational leadership dimensions like idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This research endorses the transformational leadership model within the context of 21st-century education characterized by digital predominance. This case study offers practical advice for High School 2 Takalar's principal and other educators on how to use transformational leadership to boost teacher professionalism and performance in the digital age.